Evaluation on the development degree of China's seven pilot carbon markets. Issue 1 (2nd January 2018) - Yi, Lan; Li, Zhaopeng; Yang, Li; Liu, Jie; Packianather, Michael
ABSTRACT: China is preparing to establish a nationwide carbon market in 2017, and in order to facilitate this goal, seven pilot carbon markets have been under study for the past few years. This paper summarizes the operation experience and challenges of the seven pilot carbon markets in China. It has been widely accepted that the essence of a carbon market is to solve environmental problems through market mechanisms, with environmental benefit being the fundamental purpose, market mechanism being the key measure, and policies and regulations being an important guarantee for an orderly carbon market. Therefore, this paper constructs an evaluation index system composed of 34 detailed sub-indexes in three dimensions, such as environmental constraint force, market resource allocation ability, and supporting policies and facility completeness. Through analyzing the operation data from 2013 to 2016, the weights of the sub-indexes are obtained. In addition, the study obtains experts' opinions from over 10 carbon permits exchanges, consultancy firms and research institutions in China, and conducts a comprehensive evaluation on the development degree of the seven pilot carbon markets. Results show that the pilot carbon markets that include private SMEs as the covered entities for emissions control present relatively higher environmental constraint force. But too many covered entities could increase the difficulty of market performance management, while the pilots that include high energy-consuming state-owned enterprises as the entities for emissions control demonstrate a phenomenon of "high market compliance rate with low trading volume". The resource allocation capability of China's carbon market has not been effectively brought into play, and low degree of market participation has become an important constraint factor for market development. Due to the lack of laws and regulations at the national macro-level, the legally binding force of the pilot markets construction is obviously insufficient, and the supporting policies are lacking foresights. Generally, the development of China's pilot carbon markets is still in such a fragmented state as in the aspects of environment, market and policy development, and the market operation has not yet achieved the purpose of solving environmental problems through market mechanisms. Accordingly, policy recommendations pointed out by this study are that tightening the allowance of free quota and progressively increasing the auction proportion, improving legal construction, increasing the services and products of carbon finance and standardizing the order of market transactions, enhancing capacity building of local governments and promoting the participation willingness and capability of emissions control entities, will be necessary.